THE CURRICULUM FACE OF INDONESIAN ELEMENTARY SCHOOL: CASE STUDY - Hidayati, Dian; Masa, Karolina Sriwahyu Ningsi (Universitas Pendidikan Indonesia, 2023)
Education is a human resource and vehicle to humanize itself. Through education, humans expected to be able to know themselves, establish harmonious relationships with others and the natural surroundings. This study uses descriptive qualitative; the purpose of this study is to determine the implementation of the curriculum. The research data collection uses documentation, observation, and interviews, and this research conducted at SDN 2 Jombong Boyolali district. The results showed that the implementation of the 2013 curriculum was only applied in grades II and IV, while classes I, III, and VI used KTSP. The curriculum that is continuously updated indicates that the face of our education is still too early to be at a quality level. Also, the lack of teacher competence in implementing the established curriculum influences the growth and development of our education world.